Activation of T-bet, FOXP3, and EOMES in Target Organs From Piglets Infected With the Virulent PRRSV-1 Lena Strain - Ruedas-Torres, Inés; Gómez-Laguna, Jaime; Sánchez-Carvajal, José María; Larenas-Muñoz, Fernanda; Barranco, Inmaculada; Pallarés, Francisco José; Carrasco, Librado; Rodríguez-Gómez, Irene Magdalena (Frontiers in Immunology, 2021)
Transcription factors (TFs) modulate genes involved in cell-type-specific proliferative and migratory properties, metabolic features and effector functions. Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most important pathogen agents in the porcine industry, however, TFs have been poorly studied during the course of this disease. Therefore, we aimed to evaluate the expression of T-bet, GATA3, FOXP3 and Eomesodermin (EOMES) TFs in target organs (lung, tracheobronchial lymph node and thymus) as well as the expression of different effector cytokines (IFNG, TNFA, IL10) and FASL during the early phase of infection with PRRSV-1 strains of different virulence. Targets organs from mock-, virulent Lena- and low virulent 3249-infected animals humanely euthanized at 1, 3, 6, 8 and 13 days post-infection (dpi) were collected to analyze PRRSV viral load, histopathological lesions and relative quantification through RT-qPCR of TFs and cytokines. Animals belonging to both infected groups, but mainly those infected with the virulent Lena strain, showed an upregulation of the TFs T-bet, EOMES and FOXP3 together with an increase of the cytokine IFNG in target organs at the end of the study (approximately two weeks post-infection). These results are suggestive of a stronger polarization to Th1 cells and Tregs but also CD4+ CTLs, effector CD8+ T cells and γδT cells in virulent PRRSV-1-infected animals, however, their biological functionality should be object of further studies.